Energy Optimization Using a Pump Scheduling Tool in Water Distribution Systems - Muhammed, Karwan A.; Farmani, Raziyeh (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
Water distribution management system is a costly practice and with the growth of population, the needs for creating more cost-effective solutions are vital. This paper presents a tool for optimization of pump operation in water systems. The pump scheduling tool (PST) is a fully dynamic tool that can handle four different types of fixed speed pump schedule representations (on and off, time control, time-length control, and simple control [water levels in tanks]). The PST has been developed using Visual Basic programming language and has a linkage between the EPANET hydraulic solver with the GANetXL optimization algorithm. It has a user-friendly interface which allows the simulation of water systems based on (1) a hydraulic model (EPANET) input file, (2) an interactive interface which can be modified by the user, and (3) a pump operation schedule generated by the optimization algorithm. It also has the interface of dynamic results which automatically visualizes generated solutions. The capabilities of the PST have been demonstrated by application to two real case studies, Anytown water distribution system (WDS) and Richmond WDS as a real one in the United Kingdom. The results show that PST is able to generate high-quality practical solutions.